Phaseolus talamancensis, a new wild bean species (leguminosae, phaseoline) from montane forests of eastern Costa Rica - Torres González, Alba Marina; Toro Chica, Orlando; Debouck, Daniel G. (2001)
A new species of Phaseolus (Legumi nosae, Phaseolinae) has been found in the montane forests of the Sierra de Talamanca in eastern Costa Rica, where it appears endemic. Distinctive traits include: radicant roots, purplish red internodes, veins of leaflets, primary bracts, inner face of stan dard, and wings. Differences with related taxa of Costa Rica and other parts of Central America are discussed, namely the smaller and rounded primary bracts as compared to P. macrolepis, and the radi cant fibrous root system as compared to P. xantho trichus.